Improved thermal stability and narrowed line width of photoluminescence from InGaN nanorod by ytterbium doping. Issue 4 (18th March 2015) - Wang, Jingzhou; Dasari, Kiran; Cooper, Kevin; Thota, Venkata R.; Wright, Jason; Palai, Ratnakar; Ingram, David C.; Stinaff, Eric A.; Kaya, S.; Jadwisienczak, W. M.
Abstract: Nanorod of in situ Yb‐doped InGaN and undoped InGaN have been grown on (0001) sapphire substrates by plasma assisted molecular beam epitaxy (MBE). Selected regions on Yb‐doped InGaN sample show single dominant near band edge emission (NBE) in green, yellow or orange color due to the variation of In content. Temperature dependent PL peak energy of InGaN nanorod shows the characteristic S ‐shaped behavior indicating the presents of strong exciton localization energy in undoped InGaN nanorod. The exciton localization energy reduced significantly after incorporating Yb into InGaN, giving rise to damping of the S‐shape profile amplitude and narrowing of the PL line width from ∼20 meV to ∼12 meV at 11 K. It is proposed that the improved PL thermal stability and the PL line width in Yb‐doped InGaN nanorod is affected by the Yb gettering effect. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)